2023
DOI: 10.3390/nano13040767
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide Nanoparticles Modulate Systemic Immune Response and Increase Levels of Reduced Glutathione in Mice after Seven-Week Inhalation

Abstract: Titanium dioxide nanoparticles (TiO2 NPs) are used in a wide range of applications. Although inhalation of NPs is one of the most important toxicologically relevant routes, experimental studies on potential harmful effects of TiO2 NPs using a whole-body inhalation chamber model are rare. In this study, the profile of lymphocyte markers, functional immunoassays, and antioxidant defense markers were analyzed to evaluate the potential adverse effects of seven-week inhalation exposure to two different concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Ma-Hock et al for example recommend the measurements of several inflammatory mediators in 5-day inhalation studies, including IL-6, IL-8 and TNF-α (Ma-Hock et al, 2009). Also other studies report release of inflammatory mediators after inhalation exposure to TiO 2 (Noël et al, 2013;Wang et al, 2021;Scarino et al, 2012;Lehotska Mikusova et al, 2023). RNA expression levels of TNF-α and IL-6 were increased after pulmonary exposure to silica-coated TiO 2 NMs in mice (Leppänen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ma-Hock et al for example recommend the measurements of several inflammatory mediators in 5-day inhalation studies, including IL-6, IL-8 and TNF-α (Ma-Hock et al, 2009). Also other studies report release of inflammatory mediators after inhalation exposure to TiO 2 (Noël et al, 2013;Wang et al, 2021;Scarino et al, 2012;Lehotska Mikusova et al, 2023). RNA expression levels of TNF-α and IL-6 were increased after pulmonary exposure to silica-coated TiO 2 NMs in mice (Leppänen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…12 Studies on animals and in the lab have demonstrated the dangers of excessive nanoparticle and ultrafine particle concentrations. 13 Some employees who are unintentionally exposed to extremely high amounts get lung injuries and fluid buildup around their airways. 14 Pollutants in the air of workplace can aggravate one’s respiratory health and result in “occupational asthma,” coal workers’ pneumoconiosis, chest pain, asthma spasms, coughing, and shortness of breath.…”
Section: Causes and Effects Of Air Pollution In Dhaka Citymentioning
confidence: 99%
“…However, dermal exposure via cosmetic usage and oral exposure through food additives did not show any prominent impact but their potential accumulation in the gastrointestinal tract has raised serious concerns among the developed countries. In rodent models like rats and mice, TiO 2 particles have demonstrated pulmonary in ammation, altered hepatic gene expressions and liver enzyme levels, decreased sperm quality and impaired fertility [8][9][10][11]. Similarly, in cell culture models, TiO 2 particles induced apoptosis and necrosis mechanisms, triggered pro-in ammatory cytokines in addition caused DNA damage, and chromosomal aberrations, raising concerns about their potential genotoxic effects [12,13].…”
Section: Introductionmentioning
confidence: 99%